A qualitative study of enablers and barriers influencing the incorporation of social accountability values into organisational culture: a perspective from two medical schools. Issue 1 (December 2015) - Leigh-Hunt, Nicholas; Stroud, Laura; Murdoch Eaton, Deborah; Rudolf, Mary
Abstract Background Definitions of social accountability describe the obligation of medical schools to direct education, research and service activities towards addressing the priority health concerns of the population they serve. While such statements give some direction as to how the goal might be reached, it does not identify what factors might facilitate or hinder its achievement. This study set out to identify and explore enablers and barriers influencing the incorporation of social accountability values into medical schools. Methods Semi structured interviews of fourteen senior staff in Bar Ila n and Leeds medical schools were undertaken following a literature review. Participants were recruited by purposive sampling in order to identify factors perceived to play a part in the workings of each institution. Results Academic prestige was seen as a key barrier that was dependent on research priorities and student selection. The role of champions was considered to be vital to tackle staff perceptions and facilitate progress. Including practical community experience for students was felt to be a relevant way in which the curriculum could be designed through engagement with local partners. Conclusions Successful adoption of social accountability values requires addressing concerns around potential negative impacts on academic prestige and standards. Identifying and supporting credible social accountability champions to disseminate the values throughout research and education departments in medical and other faculties is also necessary, including mapping onto existing work streams and research agendas. Demonstrating the contribution the institution can make to local health improvement and regional development by a consideration of its economic footprint may also be valuable.